2021
DOI: 10.1007/s12262-021-03081-w
|View full text |Cite
|
Sign up to set email alerts
|

Global Surgery Education and Training Programmes—a Scoping Review and Taxonomy

Abstract: Global surgery is an emerging field of study and practice, aiming to respond to the worldwide unmet need for surgical care. As a relatively new concept, it is not clear that there is a common understanding of what constitutes “global surgery education and training”. This study examines the forms that global surgery education and training programmes and interventions take in practice, and proposes a classification scheme for such activities. A scoping review of published journal articles and internet websites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 61 publications
0
16
0
4
Order By: Relevance
“…Many programs and courses in global health and global surgery are not accessible to many LMIC learners [ 41 , 42 ]. A 2021 scoping review on Global Surgery Education and Training Programmes by O’Flynn et al failed to identify any academic global surgery specific education programmes in LMICs [ 43 ]. Apart from the fact that few academic global surgery institutions are located in LMICs [ 7 , 43 ], the concept of “global surgery” is often misunderstood and the definition of this topic varies depending on context [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many programs and courses in global health and global surgery are not accessible to many LMIC learners [ 41 , 42 ]. A 2021 scoping review on Global Surgery Education and Training Programmes by O’Flynn et al failed to identify any academic global surgery specific education programmes in LMICs [ 43 ]. Apart from the fact that few academic global surgery institutions are located in LMICs [ 7 , 43 ], the concept of “global surgery” is often misunderstood and the definition of this topic varies depending on context [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many different projects in global surgery have subsequently emerged to tackle this gap in healthcare provision, despite the continuing lack of conceptual clarity on what it means to practice 'safe global surgery'. [7][8][9] Indeed, definitions of such have varied over the years, with one group framing it as 'the enterprise of providing improved and equitable surgical care to the world's population, with its core tenets as the issues of need, access and quality' and another author characterising it far more comprehensively as the 'area for study, research, practice, and advocacy that places priority on improving health outcomes and achieving health equity for all people worldwide who are affected by surgical conditions or have a need for surgical care'. 10 11 Yet, whereas the content of any singular global surgery project has varied, a systematic review of partnerships between North American and LMIC institutions found that over 81% of these projects included a surgical education component.…”
Section: Open Accessmentioning
confidence: 99%
“…Al necesitar de un sustrato significativo para poder lograr la integración de sus partes, se ha descrito que las redes de conocimiento especializado y la investigación colaborativa, facilitan el desarrollo de proyectos de investigación, entrenamiento de estudiantes, médicos residentes y cirujanos, así como el perfeccionamiento de habilidades no técnicas, las cuales juegan un rol fundamental en el cirujano de hoy, en el profesionalismo médico y en la medicina basada en la evidencia [4][5][6] . De esta forma, ha sido factible direccionar las prioridades de la cirugia global, utilizando como puente a la cirugía académica.…”
Section: Introductionunclassified
“…Esto ha sido proyectado como un compromiso moral por todas las cien-cias de la vida y de la salud, incluida la cirugía 8 . Siendo así, entonces se considera indispensable participar en consorcios y grupos colaborativos sólidos, de naturaleza local, regional, nacional e internacional, que favorezcan la apropiación social y circulación del nuevo conocimiento, el diseño y ejecución de estudios multicéntricos con muestras masivas, y el intercambio y movilidad de estudiantes y profesionales que promuevan el entrenamiento técnico y adaptación laboral, fortalezcan la malla curricular académica institucional, faciliten el acceso a financiación nacional e internacional y, permitan identificar potenciales problemas en la comunidad (Figura 1), que puedan ser resueltos a partir de la ciencia, tecnología e innovación quirúrgica [4][5][6] . Esta hoja de ruta ha sido construida y discutida a lo largo de los años, intentando acaparar todos los vacíos posibles, para poder plantear soluciones prácticas, reales y reproducibles, sobre todo, en aquellos países con mayores necesidades.…”
Section: Introductionunclassified